Pemberdayaan Masyarakat Home Industri Dalam Rangka Mendorong Kemandirian Ekonomi - Warter Agustim (BIP's JURNAL BISNIS PERSPEKTIF, 2016)
Development in harmony is needed, between the buffer zones and urban areas.Development in harmony must demonstrate the important role of buffer zones tourban areas because of the synergy potential of different regions and need eachother. So by knowing the potential of each area required mapping potential areascan provide a buffer for future development plans. This study has the objective to provide information to SMEs located in the Donowarih Village, Karangploso District., Malang Regency, which has good characteristics as a buffer zone for the surrounding urban environment. This study used a qualitative descriptive method. The study states that the majority of SMEs in the village Donowarih still using simple management in the management of its business. Many factors are influential in this regard, education, mental, environmental and other factors. Based on the need for repair and improvement programs that can improve the ability of SMEs and the other is the most important thing the government can directly determine program development program that is in harmony with the state of local characteristics.